IMPROVING STUDENT LEARNING ACTIVENESS THROUGH THE PROBLEM BASED LEARNING (PBL) MODEL IN ELEMENTARY SCHOOL - Ramlan Mahmud (Sains Global Institut, Indonesia, 2026)
This study aims to improve the learning activity of fifth-grade students at the UPT Spf SD Negeri Mamajang 1 Makassar. The type of research is classroom action research (CAR) which is carried out in 2 cycles. Each cycle consists of 4 stages: planning, implementation, observation, and reflection. Data were collected using observation techniques to obtain data on student activity. There was a change in their attitudes during the learning process with the problem-based learning (PBL) model. In cycle I, it obtained 27%. While in cycle II, it obtained 82%. Based on the data, there was a maximum increase in cycle II, which was 55%. This study aims to improve the learning activity of fifth-grade students at UPT Spf SD Negeri Mamajang 1 Makassar. The type of research is classroom action research (CAR) which is carried out in 2 cycles. Each cycle consists of 4 stages: planning, implementation, observation, and reflection. Data were collected using observation techniques to obtain data on student activity. There was a change in their attitudes during the learning process with the problem-based learning (PBL) model. In cycle I, it obtained 27%. While in cycle II it obtained 82%. Based on the data, there was a maximum increase in cycle II, which was 55%.